STRATEGI SUPERVISI AKADEMIK BERBASIS KOLABORATIF UNTUK MENINGKATKAN PROFESIONALISME GURU DAN KUALITAS PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN (SMK) MULYA BHAKTI MANDIRI - Rita Santirahayu; Nirwan Rosadi; Fitria Aprilianti; Hendri Haerudin; Dinny Mardiana (STKIP Subang, 2026)
This study is motivated by the relatively low level of teacher professionalism and the quality of learning in Vocational High Schools (SMK), as indicated by the suboptimal planning, implementation, and evaluation of learning processes. Academic supervision, which has tended to be conventional and individual in nature, has not significantly improved teacher competence. Therefore, a collaborative-based academic supervision strategy involving active participation among principals, teachers, and relevant stakeholders is needed. This study aims to analyze the planning, implementation, and outcomes of a collaborative-based academic supervision strategy in improving teacher professionalism and the quality of learning at SMK Mulya Bhakti Mandiri. The methodology employed is a qualitative approach with a case study design. Data collection techniques include interviews, observations, and documentation, with research subjects consisting of the principal, teachers, and the supervision team. Data analysis is conducted through data reduction, data display, and conclusion drawing. The results indicate that the collaborative-based academic supervision strategy effectively enhances teacher professionalism, as reflected in improved lesson planning, the use of innovative teaching methods, and more systematic evaluation practices. In addition, the quality of learning has improved, as shown by increased student engagement and better learning outcomes. Thus, collaborative-based academic supervision is proven to be an effective strategy for improving the quality of education in vocational high schools.